A comparison of indices of difference and similarity, based on LTASS and tested on voices in real forensic case and in controlled conditions - Varošanec-Škarić, Gordana (Array, 2007)
This study compares the difference of indices of difference and similarity between voices in real case and in the controlled group. The LTASS has been set for the range of 800 and 3500 Hz. This result is based on the comparisons of indices of difference (SDDD: Standard Deviation of Difference Distribution) and similarity (R) in speech recordings of standardized text read by the controlled group. The real case was 6 male voices: 5 Croatian and 1 Albanian. The controlled group was 30 male and 35 female speakers (all Croatian). To enable data comparison, average values of indices were calculated for the same and different speakers on the basis of different parts of the spectrum: from 0 to 10 kHz and filtered voices from 0.8 to 3.5 kHz. The results of t-test have shown that the groups differ significantly, and as expected the difference was greatest respectively in the group of male voices recorded in the studio (0-10 kHz: p<0.001, t=46.17) ; filtered studio voices (p<0.001) ; and real case (p<0.01). It is of methodological importance that in real case the difference of SDDD indices between different and same pairs of voices was significant (p<0.01), as well as the difference of similarity indices (p=0.01).